1989
DOI: 10.1038/hdy.1989.32
|View full text |Cite
|
Sign up to set email alerts
|

Environmental correlates of inversion frequencies in natural populations of seaweed flies (Coelopa frigida)

Abstract: Two populations of seaweed flies (Coelopa frigida) from the north-east coast of England were sampled at approximately monthly intervals. Single samples were also collected from populations on the south coast. The allele and genotype frequencies at the alcohol dehydrogenase locus, known to be associated with the large a/13 chromosomal inversion, were determined for each of the 34 samples.Aspects of the habitats were quantified at the time of sampling, as were 12 variables extracted from meteorological data. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1

Year Published

1992
1992
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 19 publications
3
26
1
Order By: Relevance
“…Changes in inversion frequencies were often interpreted in terms of inversion heterozygote advantage, particularly as an excess of heterokaryotypes was found in several population samples. This pattern has also been observed in population samples of Anopheles gambiae mosquitoes (Brooke et al 2002) and Coelopa frigida flies (Butlin & Day 1989). …”
Section: Frequency Changes In Populationssupporting
confidence: 65%
See 1 more Smart Citation
“…Changes in inversion frequencies were often interpreted in terms of inversion heterozygote advantage, particularly as an excess of heterokaryotypes was found in several population samples. This pattern has also been observed in population samples of Anopheles gambiae mosquitoes (Brooke et al 2002) and Coelopa frigida flies (Butlin & Day 1989). …”
Section: Frequency Changes In Populationssupporting
confidence: 65%
“…In blackflies and seaweed flies, they influence development time. In seaweed flies they also influence size and viability, although trait effects vary with environmental conditions including density (Butlin & Day 1989). Chromosome inversions also influence sperm displacement in seaweed flies; when females mate rapidly with males carrying the same or different karyotypes, sperm from males with the opposite karyotype to the female are favored, resulting in a higher number of heterokaryotypic offspring (Blyth & Gilburn 2005).…”
Section: Candidate Traitsmentioning
confidence: 99%
“…Predation by birds certainly occurs, but we have no evidence to suggest that it is selective with respect to the afl inversion system. In contrast, adverse physical conditions do result in differential mortality (Day et al, 1983;Butlin & Day, 1989), with heterokaryotypes exhibiting the highest fitness. The present study showed that larval competition results in a similar pattern of mortality to these climatic factors, which will make it extremely difficult to distinguish their effects.…”
Section: Discussionmentioning
confidence: 87%
“…The Adh-B allele is always associated with the a form of the inversion, and the D allele with the p form. This genetic polymorphism is stable both temporally and spatially (Day et al, 1983;Butlin & Day, 1989), and is maintained as a result of the superior fitness of as heterokaryotypes; in almost all samples taken from natural populations there is a significant excess of heterokaryotypes over Hardy-Weinberg expectations (Butlin et al, 1982: Day et al, 1983Gilburn & Day, 1994). Preliminary evidence from laboratory culture suggested that the excess of heterokaryotypes increases with larval density .…”
Section: Introductionmentioning
confidence: 96%
“…One such character is adult size. The phenotypic variation in adult size is very much greater in males than females (Butlin et al, 1982a,b;Day et a!., 1982), and it is the largest males that consistently exhibit the lowest survival from egg to adult (Collins, 1978;Butlin et al, 1982aButlin et al, , 1984Butlin & Day, 1989). A very much weaker candidate to be the preferred character is the genotype at the Adh locus, which was used by Engelhard et al (1989) andFoster (1989) to study male mating success.…”
Section: Introductionmentioning
confidence: 99%